Glucose Abnormalities Associated to Prolactin Secreting Pituitary Adenomas - Auriemma, Renata S.; De Alcubierre, Dario; Pirchio, Rosa; Pivonello, Rosario; Colao, Annamaria (Frontiers in Endocrinology, 2019)
Hyperprolactinaemia has been implicated in the pathogenesis of obesity and abnormalities in glucose metabolism, and is reportedly associated with metabolic syndrome in approximately one third of patients. Insulin secretion and β-cell proliferation increase following the exposure of isolated pancreatic islet to PRL, and overexpression of PRL in β-cells leads to inappropriately elevated serum insulin concentrations, increased islet insulin content and sustained β-cell replication. PRL excess has been found to reduce glucose tolerance and to induce hyperinsulinemia, leading to insulin resistance in both obese and lean patients. Human pancreatic -cell and adipocytes abundantly express dopamine receptor type 2, suggesting a regulatory role for peripheral dopamine in insulin and adipose functions. Medical treatment with the dopamine-agonists bromocriptine and cabergoline significantly improves glucose abnormalities and reduces the prevalence of metabolic syndrome. In patients with concomitant hypogonadism, simultaneous correction of testosterone deficiency, besides hyperprolactinemia, ameliorates insulin resistance and abnormalities in glucose metabolism. Therefore, in patients with PRL-secreting pituitary adenomas control of PRL excess by dopamine agonists is mandatory to improve glucose and insulin abnormalities.